2019
DOI: 10.1111/jems.12311
|View full text |Cite
|
Sign up to set email alerts
|

Managing competition on a two‐sided platform

Abstract: On many two-sided platforms, users on one side not only care about user participation and usage levels on the other side, but they also care about participation and usage of fellow users on the same side. Most prominent is the degree of seller competition on a platform catering to buyers and sellers. In this paper, we address how seller competition affects platform pricing, product variety, and the number of platforms that carry trade. K E Y W O R D S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…For instance,Lee (2013) found that the video game industry features poor substitutability of videogames and the presence of a handful number of Superstar titles which can impact console sales by as much as 5%. For a model with competing firms on the seller side, see e.g.,Belleflamme & Toulemonde (2009),Belleflamme & Peitz (2019a),Karle et al (2019). 15 This is partly similar to what presented byKourandi et al (2015), who study the contractual decision made by Internet Service Providers to content providers.…”
supporting
confidence: 60%
“…For instance,Lee (2013) found that the video game industry features poor substitutability of videogames and the presence of a handful number of Superstar titles which can impact console sales by as much as 5%. For a model with competing firms on the seller side, see e.g.,Belleflamme & Toulemonde (2009),Belleflamme & Peitz (2019a),Karle et al (2019). 15 This is partly similar to what presented byKourandi et al (2015), who study the contractual decision made by Internet Service Providers to content providers.…”
supporting
confidence: 60%
“…This growth mostly depends on a sentence/decision of the Autorità Garante della Concorrenza e del Mercato (Italian antitrust) that has freed taxi drivers to use more than a single platform (traditional or digital) to get the rides. These data show that this platform can be considered as a good example of best practice, and so it is interesting to explore and describe the main strategies its management has designed and implemented to reduce the complexity embedded in the chicken and egg paradox and to leverage effectively the interconnection between the two subsystems (both passengers and taxi drivers) to create a stronger set of value creation processes that enhance the possibility of platform diffusion (Evans et al, 2011;Belleflamme and Peitz, 2018;Mäntymäki et al, 2019;Wang and Yang, 2019) and increasing its chances of an emergent behavior (Walby, 2007;Galkina and Atkova, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Multi-homing of consumers is an important feature of online markets. It has also been discussed extensively in the literature such as Athey et al (2016), Belleflamme & Peitz (2019a), Bakos & Halaburda (2019) and others. 34 .…”
Section: Multi-homing Consumersmentioning
confidence: 99%